Hydrogen fuel cell catalyst and preparation method thereof

By loading the Pt-Ru bimetallic coating on the Nb-TiO2 carrier, the problem of degradation of stability caused by the corrosion of the carbon support is solved, and the durability and safety performance of the fuel cell are improved.

CN119481114APending Publication Date: 2025-02-18WUXI WEIFU ENVIRONMENT PROTECTION CATALYST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411644598.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing hydrogen fuel cell catalysts have reduced stability due to corrosion of carbon support, which affects the durability of fuel cells.

Method used

Nb-TiO2 is used as a non-carbon support and a Pt-Ru bimetallic coating is loaded thereon. Through the introduction of Ru elements and the appropriate Pt/Ru ratio, the conductivity and stability of the catalyst are improved and carbon corrosion is avoided.

Benefits of technology

It effectively improves the durability and safety performance of the fuel cell, extends the electrolytic reaction time during the reverse pole, and reduces the amount of precious metals and the cost of catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481114A_ABST
    Figure CN119481114A_ABST
Patent Text Reader

Abstract

The invention provides a hydrogen fuel cell catalyst, and relates to the technical field of catalysts, the hydrogen fuel cell catalyst comprises an Nb-TiO2 carrier and an active coating loaded on the Nb-TiO2 carrier, the active coating is a Pt-Ru bimetallic coating, and the atomic ratio of Pt to Ru in the active coating is (5-1): (1-5). According to the hydrogen fuel cell catalyst and the preparation method thereof, the Nb-TiO2 carrier and the active coating loaded on the Pt-Ru / Nb-TiO2 carrier, the active coating is a Pt-Ru bimetal coating, the problem of carbon corrosion is solved by selecting Nb-TiO2 as the carrier, the Ru element is introduced while the non-carbon carrier is used, the electrolyzed water reaction time in the antipole period can be prolonged, and the hydrogen fuel cell catalyst has the advantages that the reaction time is shortened, the service life of the hydrogen fuel cell catalyst is prolonged, the service life of the hydrogen fuel cell catalyst is prolonged, and the service life of the hydrogen fuel cell catalyst is prolonged. Meanwhile, due to the proper proportion of Pt and Ru, the catalytic performance and the corrosion-resistant effect of the catalyst can be considered, and the catalyst is suitable for being applied to the fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, in particular to a hydrogen fuel cell catalyst and a preparation method thereof. Background Art

[0002] As fossil energy is becoming increasingly depleted, it is urgent to find alternative new energy sources. Hydrogen energy, as an efficient, clean, safe and sustainable secondary energy source, has attracted much attention in recent years. Hydrogen energy can penetrate into all aspects of traditional energy, including transportation, long-term energy storage, industrial fuel, portable equipment and other fields. Hydrogen fuel cells have excellent performance in hydrogen energy utilization efficiency, power density, emissions and other aspects, and are considered to have broad development prospects.

[0003] As the core material of hydrogen fuel cells, catalysts account for a large proportion of the entire fuel cell stack cost; the initial activity and stability of the catalyst are important indicators to measure its performance, however, the catalyst often affects the life of the fuel cell due to the decline in stability; the main factors causing the decline in catalyst stability include catalyst decomposition, sintering, agglomeration and corrosion of the carbon carrier, and the corrosion of the carbon carrier material is the main cause of catalyst failure.

[0004] Therefore, it is very necessary to find non-carbon carriers with stable performance under fuel cell working conditions to replace the carbon carrier materials commonly used in catalysts to improve the durability of fuel cells. Replacing carbon carriers with Nb-TiO2 carriers can improve the durability of fuel cells. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a hydrogen fuel cell catalyst and a preparation method thereof. A specific content of Ru element can improve the overall performance of the catalyst. At the same time, the Nb-TiO2 carrier replaces the carbon carrier. The two work synergistically to improve the conductivity and stability of the catalyst, and effectively get rid of the carbon corrosion caused by the reverse pole of the fuel cell, thereby protecting the structure and performance of the fuel cell catalyst layer, improving the durability of the fuel cell, and improving the safety performance of the battery.

[0006] The technical solution adopted by the present invention is: A hydrogen fuel cell catalyst, comprising: a Nb-TiO2 carrier, an active coating loaded on the Nb-TiO2 carrier, wherein the active coating is a Pt-Ru bimetallic coating, and the atomic ratio of Pt to Ru in the active coating is 5-1:1-5.

[0007] Preferably, in the hydrogen fuel cell catalyst, the mass ratio of the Nb-TiO2 carrier to the Pt-Ru bimetallic coating is 30~70:30~70.

[0008] The present invention also provides a method for preparing a hydrogen fuel cell catalyst, which comprises the following steps: Step S1. Mixing of bimetallic Pt and Ru: weighing a platinum precursor and a ruthenium precursor respectively according to an atomic ratio of Pt to Ru of 5-1:1-5, then adding the platinum precursor and the ruthenium precursor to deionized water respectively, stirring for 0.5-1h, and mixing to obtain a mixed solution; Step S2. Pt-Ru / Nb-TiO2 loading: Weigh Nb-TiO2 according to the mass ratio of Nb-TiO2 carrier to Pt-Ru bimetallic coating of 30-70:30-70, and add Nb-TiO2 to the mixed solution of step S1, and mix by ultrasonic to obtain slurry; Step S3. Hydrothermal reaction: adding the slurry into a reactor for hydrothermal reaction, and after the hydrothermal reaction, filtering and washing the slurry to remove impurity ions to obtain a filter cake; Step S4. Catalyst drying: drying the filter cake from step S3 to obtain a hydrogen fuel cell catalyst.

[0009] Preferably, in the method for preparing the hydrogen fuel cell catalyst, the platinum precursor in step S1 is selected from one or more of chloroplatinic acid, potassium chloroplatinite, platinum acetylacetonate, and dinitrosodiammineplatinum nitric acid solution.

[0010] Preferably, in the method for preparing the hydrogen fuel cell catalyst, the ruthenium precursor in step S1 is selected from any one or more of ruthenium trichloride, potassium chlororuthenate and ruthenium acetate.

[0011] Preferably, in the method for preparing the hydrogen fuel cell catalyst, the Nb doping amount of Nb-TiO2 in step S2 is 1-10%.

[0012] Preferably, in the method for preparing the hydrogen fuel cell catalyst, the hydrothermal temperature in step S2 is 120-200° C. and the reaction time is 4-8 hours.

[0013] Preferably, in the method for preparing the hydrogen fuel cell catalyst, the cleaning solvent in step S2 is water, and the number of cleaning times is 10 to 20 times.

[0014] Preferably, in the method for preparing the hydrogen fuel cell catalyst, the drying temperature in step S2 is 160-200° C. and the drying time is 15-20 hours.

[0015] Advantages of the present invention: The hydrogen fuel cell catalyst of the present invention and its preparation method include a Nb-TiO2 carrier and an active coating loaded on a Pt-Ru / Nb-TiO2 carrier, wherein the active coating is a Pt-Ru bimetallic coating. The carbon corrosion problem is solved by selecting Nb-TiO2 as a carrier. While using a non-carbon carrier, the Ru element is introduced, which can extend the water electrolysis reaction time during the reverse polarity period and effectively improve the durability of the fuel cell. Meanwhile, the appropriate Pt and Ru ratio can take into account the catalytic performance and corrosion resistance of the catalyst itself, and is suitable for the application of fuel cells. The Nb-TiO2 loading process is adopted to reduce the amount of precious metals used and reduce the catalyst cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a durability test diagram of Examples 1-3 of the present invention.

[0017] Figure 2 This is a durability test diagram of Example 1 of the present invention.

[0018] Figure 3 This is a diagram of the anti-reverse polarity performance of Example 1 of the present invention.

[0019] Figure 4 It is a diagram of the anti-reverse polarity performance of comparative example 1 of the present invention.

[0020] Figure 5 It is a diagram of the anti-reverse polarity performance of comparative example 2 of the present invention. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with specific embodiments.

[0022] Example 1 A hydrogen fuel cell catalyst comprises a Nb-TiO2 carrier and an active coating loaded on the Pt-Ru / Nb-TiO2 carrier, wherein the active coating is a Pt-Ru bimetallic coating, and the atomic ratio of Pt to Ru in the active coating is 5:1.

[0023] The method for preparing the hydrogen fuel cell catalyst of this embodiment comprises the following steps: Step S1. Adding bimetallic Pt and Ru: Weigh chloroplatinic acid and ruthenium trichloride hydrate respectively according to the atomic ratio of Pt to Ru being 5:1, then add chloroplatinic acid and ruthenium trichloride hydrate respectively into deionized water, stir for 0.5h, and mix, then add 0.5M NaOH solution to adjust the pH to 10 to obtain a mixed solution; Step S2. Pt-Ru / Nb-TiO2 loading: Weigh Nb-TiO2 according to the mass ratio of Nb-TiO2 carrier and Pt-Ru bimetallic coating of 40:60, the Nb doping amount of Nb-TiO2 is 5%, and add Nb-TiO2 to the mixed solution of step S1, and mix by ultrasonic for 1 hour to obtain slurry; The preparation method of Nb-TiO2 carrier is as follows: 4 ml of tetrabutyl titanate and 46 ml of ethanol are vigorously stirred under argon atmosphere, 155 ml of ethanolic niobium is injected with a syringe, and then the mixture is continuously stirred and placed in a petri dish for drying and grinding at 100°C, crystallized in a tube furnace at 400°C in air atmosphere, raised to 600°C in argon atmosphere, introduced hydrogen for 4 hours, and cooled to room temperature to obtain Nb-TiO2; Step S3. Hydrothermal reaction: adding the slurry to a reactor for hydrothermal reaction, the hydrothermal temperature is 150°C, the reaction time is 6 hours, after the hydrothermal reaction is completed, the slurry is filtered and washed to remove impurity ions, the washing solvent is water, the washing times are 20 times, and a filter cake is obtained; Step S4. Catalyst drying: drying the filter cake of step S3 at a drying temperature of 180° C. for 20 h to obtain a hydrogen fuel cell catalyst.

[0024] Example 2 A hydrogen fuel cell catalyst comprises a Nb-TiO2 carrier and an active coating loaded on the Pt-Ru / Nb-TiO2 carrier, wherein the active coating is a Pt-Ru bimetallic coating, and the atomic ratio of Pt to Ru in the active coating is 2:1.

[0025] The method for preparing the hydrogen fuel cell catalyst of this embodiment comprises the following steps: Step S1. Adding bimetallic Pt and Ru: Weighing chloroplatinic acid crystals and ruthenium trichloride hydrate respectively according to the atomic ratio of Pt to Ru being 2:1, then adding chloroplatinic acid crystals and ruthenium trichloride hydrate respectively into deionized water, stirring for 0.5h, and mixing to obtain a mixed solution; Step S2. Pt-Ru / Nb-TiO2 loading: Weigh Nb-TiO2 according to the mass ratio of Nb-TiO2 carrier and Pt-Ru bimetallic coating of 40:60, the Nb doping amount of Nb-TiO2 is 5%, and add Nb-TiO2 to the mixed solution of step S1, and mix by ultrasonic for 1 hour to obtain slurry; The preparation method of Nb-TiO2 carrier is as follows: 4 ml of tetrabutyl titanate and 46 ml of ethanol are vigorously stirred under argon atmosphere, 155 ml of ethanolic niobium is injected with a syringe, and then the mixture is continuously stirred and placed in a petri dish for drying and grinding at 100°C, crystallized in a tube furnace at 400°C in air atmosphere, raised to 600°C in argon atmosphere, introduced hydrogen for 4 hours, and cooled to room temperature to obtain Nb-TiO2; Step S3. Hydrothermal reaction: adding the slurry to a reactor for hydrothermal reaction, the hydrothermal temperature is 150°C, the reaction time is 6 hours, after the hydrothermal reaction is completed, the slurry is filtered and washed to remove impurity ions, the washing solvent is water, the washing times are 20 times, the conductivity of the filtrate is washed to less than 5μs / cm, the solid part is retained, and a filter cake is obtained; Step S4. Catalyst drying: drying the filter cake of step S3 at a drying temperature of 180° C. for 20 h to obtain a hydrogen fuel cell catalyst.

[0026] Example 3 A hydrogen fuel cell catalyst comprises a Nb-TiO2 carrier and an active coating loaded on the Pt-Ru / Nb-TiO2 carrier, wherein the active coating is a Pt-Ru bimetallic coating, and the atomic ratio of Pt to Ru in the active coating is 1:1.

[0027] The method for preparing the hydrogen fuel cell catalyst of this embodiment comprises the following steps: Step S1. Adding bimetallic Pt and Ru: Weighing chloroplatinic acid crystals and ruthenium trichloride hydrate respectively according to the atomic ratio of Pt to Ru being 1:1, then adding chloroplatinic acid crystals and ruthenium trichloride hydrate respectively into deionized water, stirring for 0.5h, and mixing to obtain a mixed solution; Step S2. Pt-Ru / Nb-TiO2 loading: Weigh Nb-TiO2 according to the mass ratio of Nb-TiO2 carrier and Pt-Ru bimetallic coating of 40:60, the Nb doping amount of Nb-TiO2 is 5%, and add Nb-TiO2 to the mixed solution of step S1, and mix by ultrasonic for 1 hour to obtain slurry; Step S3. Hydrothermal reaction: adding the slurry to a reactor for hydrothermal reaction, the hydrothermal temperature is 150°C, the reaction time is 6 hours, after the hydrothermal reaction is completed, the slurry is filtered and washed to remove impurity ions, the washing solvent is water, the washing times are 20 times, and a filter cake is obtained; Step S4. Catalyst drying: drying the filter cake of step S3 at a drying temperature of 180° C. for 20 h to obtain a hydrogen fuel cell catalyst.

[0028] Comparative Example 1 A hydrogen fuel cell catalyst comprises an XC-72 carrier and an active coating loaded on the XC-72 carrier, wherein the active coating is a Pt coating.

[0029] The preparation method of the hydrogen fuel cell catalyst of this comparative example comprises the following steps: Step S1. Weigh 2 g of XC-72, add it to 200 g of ethylene glycol solution, mix it by ultrasonication, and emulsify it by shearing to obtain a mixed solution, slowly drop 3 g of 1% Pt content chloroplatinic acid solution into the mixed solution, mix it by ultrasonication for 0.5 h, and emulsify it by shearing for 0.5 h to obtain a slurry; Step S2. Hydrothermal reaction: add the slurry to a reactor and heat and reduce it at 160°C for 8 hours, filter and wash the slurry after the hydrothermal reaction to remove the impurity ions therein, wash it 20 times, wash it until the conductivity of the filtrate is less than 5μs / cm, and retain the solid part; Step S3. Catalyst drying: Place the solid part in a vacuum drying oven, set the temperature to 180° C., and dry it for 20 h.

[0030] Comparative Example 2 A hydrogen fuel cell catalyst comprises an XC-72 carrier and an active coating loaded on the XC-72 carrier, wherein the active coating is a Pt-Ru bimetallic coating, and the atomic ratio of Pt to Ru in the active coating is 5:1.

[0031] The preparation method of the hydrogen fuel cell catalyst of this comparative example comprises the following steps: Step S1. Feeding of bimetallic Pt and Ru: Weigh 2 g of XC-72, add it to 200 g of ethylene glycol solution, mix it by ultrasonication, and emulsify it by shearing to obtain a first mixed solution, weigh 2.5 g of chloroplatinic acid and 0.5 g of ruthenium trichloride hydrate according to the atomic ratio of Pt to Ru being 5:1, then add chloroplatinic acid and ruthenium trichloride hydrate to deionized water, stir for 0.5 h, and mix, then add 0.5 M NaOH solution to adjust the pH to 10 to obtain a second mixed solution; Step S2. Pt-Ru / Nb-TiO2 loading: weigh the first mixed solution and the second mixed solution according to the mass ratio of XC-72 carrier and Pt-Ru bimetallic coating of 40:60, and add the second mixed solution to the first mixed solution of step S1, and mix by ultrasonic for 1 hour to obtain slurry; Step S3. Hydrothermal reaction: adding the slurry to a reactor for hydrothermal reaction, the hydrothermal temperature is 150°C, the reaction time is 6 hours, after the hydrothermal reaction is completed, the slurry is filtered and washed to remove impurity ions, the washing solvent is water, the washing times are 20 times, and a filter cake is obtained; Step S4. Catalyst drying: drying the filter cake of step S3 at a drying temperature of 180° C. for 20 h to obtain a hydrogen fuel cell catalyst.

[0032] The catalysts prepared in Examples 1-3 and Comparative Examples 1-2 were used to prepare membrane electrodes, and single cell tests were performed. The specific test steps are as follows: Step 1. The catalysts prepared in Examples 1-3 and Comparative Examples 1-2 were mixed with isopropanol and deionized water to prepare catalyst slurry, which was sprayed on the Nafion proton membrane to obtain the anode catalyst layer of the fuel cell. The catalyst slurry prepared by Pt / C catalyst was sprayed on the other side to obtain the cathode catalyst layer, which was prepared into a membrane electrode and passed the single cell test, wherein the membrane electrode size was 5×5 cm and the cathode Pt loading was 0.3 mg / cm 2 , the anode Pt loading is 0.1 mg / cm 2 .

[0033] Step 2. Performance test, the test cell temperature is 80°C, the dew point temperature of the anode and cathode is 65°C, air is introduced into the cathode side, hydrogen is introduced into the anode side, the back pressure of the anode and cathode is 150 kPa, and the stoichiometric ratio of H2 / air is 1.5:2.5.

[0034] Step 3. Durability test: set the voltage in the range of 0.6V-0.95V, set the scanning speed to 100mV / s, repeat the potential scanning 30,000 times, and perform membrane electrode test after the scanning to examine the durability of Pt-Ru / Nb-TiO2 catalyst.

[0035] Step 4. Anti-reverse polarity performance test, the catalysts prepared in Example 1 and Comparative Example 1 are respectively mixed with isopropanol and deionized water to prepare catalyst slurry, the catalyst slurry is sprayed on the Nafion proton membrane to obtain the anode catalyst layer of the fuel cell, and the catalyst slurry prepared by Pt / C catalyst is sprayed on the other side to obtain the cathode catalyst layer, and the membrane electrode is prepared and assembled into a single cell for testing, and the battery reverse polarity is induced by fuel starvation, that is, under normal operating conditions of the battery, the anode hydrogen is replaced by nitrogen, and the power supply outputs 0.2A / cm to the battery 2 The current was used to test the anti-reverse polarity performance of the fuel cell. The cut-off voltage was -1V. After 50 times of reverse polarity, the fuel cell was recorded at 1A / cm 2 The voltage attenuation ratio at the point is as follows: Figure 2 and Figure 3 .

[0036] Figure 1 The test results show that Examples 1-3 and Comparative Example 2 exhibit higher membrane electrode activity, 1A / cm 2 The operating voltage is greater than 0.75V, 2A / cm2 The lower operating voltage is greater than 0.65V; Figure 2 After 30,000 potential scans, the membrane electrode activity did not show a significant decrease, 1A / cm 2 The operating voltage is greater than 0.71V, 2A / cm 2 The operating voltage reaches 0.63V. Figure 3 After 50 cycles of reverse polarity, the single cell of Example 1 was 2 The voltage at the point only decays by 0.53%. Figure 4 After 50 cycles of reverse polarity, the single cell of Comparative Example 1 was 2 The voltage at the point is attenuated by 12.88%. Figure 5 Comparative Example 2 Single Cell at 1A / cm 2 The voltage at the position is attenuated by 10.26%, indicating that the anti-reverse polarity catalyst provided by the present invention can effectively reduce the damage to the performance of the fuel cell caused by frequent reverse polarity.

[0037] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A hydrogen fuel cell catalyst, characterized in that: The invention comprises a Nb-TiO2 carrier and an active coating loaded on the Nb-TiO2 carrier. The active coating is a Pt-Ru bimetallic coating. The atomic ratio of Pt to Ru in the active coating is 5-1:1-5.

2. The hydrogen fuel cell catalyst according to claim 1, characterized in that: The mass ratio of Nb-TiO2 carrier and Pt-Ru bimetallic coating is 30~70:30~70.

3. The method for preparing a hydrogen fuel cell catalyst according to any one of claims 1 to 2, characterized in that: The steps include: Step S1. Mixing of bimetallic Pt and Ru: weighing a platinum precursor and a ruthenium precursor respectively according to an atomic ratio of Pt to Ru of 5-1:1-5, then adding the platinum precursor and the ruthenium precursor to deionized water respectively, stirring for 0.5-1h, and mixing to obtain a mixed solution; Step S2. Pt-Ru / Nb-TiO2 loading: Weigh Nb-TiO2 according to the mass ratio of Nb-TiO2 carrier to Pt-Ru bimetallic coating of 30-70:30-70, and add Nb-TiO2 to the mixed solution of step S1, and mix by ultrasonic to obtain slurry; Step S3. Hydrothermal reaction: adding the slurry into a reactor for hydrothermal reaction, and after the hydrothermal reaction, filtering and washing the slurry to remove impurity ions to obtain a filter cake; Step S4. Drying: Dry the filter cake from step S3 to obtain a hydrogen fuel cell catalyst.

4. The method for preparing a hydrogen fuel cell catalyst according to claim 3, characterized in that: In step S1, the platinum precursor is selected from one or more of chloroplatinic acid, potassium chloroplatinate, platinum acetylacetonate, and dinitrosodiammineplatinum nitric acid solution.

5. The method for preparing a hydrogen fuel cell catalyst according to claim 3, characterized in that: In step S1, the ruthenium precursor is selected from any one or more of ruthenium trichloride, potassium chlororuthenate and ruthenium acetate.

6. The method for preparing a hydrogen fuel cell catalyst according to claim 3, characterized in that: The Nb doping amount of Nb-TiO2 in step S2 is 1-10%.

7. The method for preparing a hydrogen fuel cell catalyst according to claim 3, characterized in that: In step S2, the hydrothermal temperature is 120-200° C., and the reaction time is 4-8 hours.

8. The method for preparing a hydrogen fuel cell catalyst according to claim 3, characterized in that: In step S2, the cleaning solvent is water, and the number of cleaning times is 10 to 20 times.

9. The method for preparing a hydrogen fuel cell catalyst according to claim 3, characterized in that: In step S2, the drying temperature is 160-200° C. and the drying time is 15-20 hours.